pVHL/HIF-regulated CD70 expression is associated with infiltration of CD27+ lymphocytes and increased serum levels of soluble CD27 in clear cell renal cell carcinoma - Ruf, Melanie; Mittmann, Christiane; Nowicka, Anna M.; Hartmann, Arndt; Hermanns, Thomas; Poyet, Cedric; Van Den Broek, Maries; Sulser, Tullio; Moch, Holger; Schraml, Peter (Clinical Cancer Research, 2015)
CD70, a member of the TNF ligand superfamily, has been shown frequently overexpressed in clear cell renal cell carcinoma (ccRCC). The mechanisms of CD70's upregulation and its role in ccRCC are unknown.CD70 expression was immunohistochemically analyzed in 667 RCCs and RCC metastases. Von Hippel-Lindau gene (VHL) mutations, expression patterns of VHL protein (pVHL), hypoxia-inducible factor (HIF) ?, and several HIF targets were studied in tissues and cell lines and correlated with CD70 overexpression. Gene promoter analysis was performed to confirm CD70 as HIF target gene. Consecutive tissue sections were immunostained to reveal the relation between CD70-expressing RCCs and tumor-infiltrating lymphocytes positive for the CD70 receptor (CD27). CD70-mediated release of soluble CD27 in RCC was assessed by coculture experiments and sera analysis of patients with RCC.Elevated CD70 expression was seen in 80% of primary tumors and metastases of ccRCC and correlated with dysregulation of the pVHL/HIF pathway. In vitro analyses demonstrated that CD70 upregulation is driven by HIF. Furthermore, CD27(+) lymphocytes preferentially infiltrate CD70-expressing ccRCCs. CD70-dependent release of soluble CD27 in cocultures may explain the high CD27 levels observed in sera of patients with CD70-expressing ccRCC. The combination of lymphocyte infiltration and CD70 expression in RCC was associated with worse patient outcome.Our findings demonstrate that in ccRCC, CD70 expression is regulated by HIF as a consequence of pVHL inactivation. Increased serum levels of CD27 suggest the existence of CD70-expressing ccRCC, thus representing a potential serum marker for patients suffering from this disease.
EVALuna2:6795